Social Deprivation and Exclusion of Immigrants in Germany - John P. Haisken-DeNew; Mathias Sinning (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
This paper aims at providing empirical evidence on social exclusion of immigrants in Germany. We demonstrate that when using a conventional definition of the social inclusion index typically applied in the literature, immigrants appear to experience a significant degree of social deprivation and exclusion, confirming much of the economic literature examining the economic assimilation of immigrants in Germany. We propose a weighting scheme that weights components of social inclusion by their subjective contribution to an overall measure of life satisfaction.Using this weighting scheme to calculate an index of social inclusion, we find that immigrants are in fact as "included" as Germans. This result is driven strongly by the disproportionately positive socio-demographic characteristics that immigrants possess as measured by the contribution to their life satisfaction.
Keywords: F22; I31; Z13; 330; Social Exclusion; International Migration; Integration